2013
DOI: 10.1136/oemed-2012-101062
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of paternal occupational exposures and the risk of childhood sporadic bilateral retinoblastoma

Abstract: Background The risk factors for sporadic (i.e. non-familial) retinoblastoma remain largely unknown. However, some studies have suggested a role for paternal work activities, primarily in farming and the metalworking industry, in the development of childhood retinoblastoma. Objectives We examined the relationship between paternal occupational exposures from jobs held 10 years and one year prior to conception and the risk of sporadic bilateral retinoblastoma in children. Methods Paternal occupational data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
0
17
0
1
Order By: Relevance
“…Only one study found paternal employment-related pesticide exposure in both the 10 years and 1 year before conception to be associated with offspring sporadic bilateral retinoblastoma (OR: 1.64, 95% CI: 1.08 to 2.50 and OR: 2.12, 95% CI: 1.25 to 3.61, respectively) 7. The study also found that higher levels of pesticide exposure (compared with moderate or none) relate to higher risks of bilateral disease.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Only one study found paternal employment-related pesticide exposure in both the 10 years and 1 year before conception to be associated with offspring sporadic bilateral retinoblastoma (OR: 1.64, 95% CI: 1.08 to 2.50 and OR: 2.12, 95% CI: 1.25 to 3.61, respectively) 7. The study also found that higher levels of pesticide exposure (compared with moderate or none) relate to higher risks of bilateral disease.…”
Section: Discussionmentioning
confidence: 97%
“…Parental occupational agents of interest were the same as in a previous study of paternal occupational exposures and sporadic bilateral retinoblastoma7 and included pesticides, welding fumes, non-welding metals, sulfur dioxide (SO 2 ), polycyclic aromatic hydrocarbons (PAH), ionising radiation, paints, chlorinated and non-chlorinated volatile organic compounds (VOCs) and non-paint VOCs. These agents have previously been associated with risk for childhood cancers 7 9 11–17…”
Section: Methodsmentioning
confidence: 99%
“…Retinoblastoma has been related to residential exposure to air pollution, 79 parental occupational exposure to oil mists 10 and to parental employment in radio or television repair 11 , shoe or leather work 12 , electrical work, 12 or in the metal industry. 13, 14 Although the literature has shown fairly consistent associations between the home use of insecticides or herbicides and other childhood cancer types, 15, 16 thus far, findings on retinoblastoma have been equivocal. Parental employment as a pesticide applicator 17 or in horticultural, forestry or farm work 1820 has been associated with a null or even weakly decreased risk for “childhood eye cancer” (all types combined) or retinoblastoma in previous studies, with the exception of the Agricultural Health Study that reported a higher risk (SIR,1.63; CI, 0.41–6.53) with wide confidence intervals.…”
Section: Introductionmentioning
confidence: 99%
“…Parental employment as a pesticide applicator 17 or in horticultural, forestry or farm work 1820 has been associated with a null or even weakly decreased risk for “childhood eye cancer” (all types combined) or retinoblastoma in previous studies, with the exception of the Agricultural Health Study that reported a higher risk (SIR,1.63; CI, 0.41–6.53) with wide confidence intervals. 21 Only one study 22 found parental employment-related pesticide exposure to be associated with offspring bilateral retinoblastoma (OR, 2.12; CI, 1.25–3.61). For unilateral disease, increased risk was observed among children whose maternal grandfathers were farmers (OR, 10.0; CI, 1.4–433).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation